2022
DOI: 10.3390/microorganisms10102052
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Use of Trimethyl Chitosan for Removing Microcystis aeruginosa in Water Treatment Processes

Abstract: The increase in cyanobacterial blooms linked to climate change and the eutrophication of water bodies is a global concern. The harmful cyanobacterium Microcystis aeruginosa is one of the most common bloom-forming species whose removal from fresh water and, in particular, from that used for water treatment processes, remains a crucial goal. Different biodegradable and environmentally friendly coagulants/flocculants have been assayed, with chitosan showing a very good performance. However, chitosan in its origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The presence of a band at 547 and 748 cm −1 in the spectra is a fingerprint of zinc-oxide vibration that underwent structural changes from the 471-614 cm −1 identified in the spectra of uncoated TM@ZnO NPs. Other authors also reported similar peaks indicating the surface coating of ZnO NPs with chitosan biopolymer [21,28,43,46]. The spectral profiles of TM@ZnO/TMC NC hydrogel on interaction with E. coli underwent some conformational changes in the broad peaks assigned to the stretching vibrations of the amines and -OH (3000-3129 cm −1 ).…”
Section: E Coli-tm@zno/tmc Nc Hydrogel Adsorption Interactionmentioning
confidence: 54%
See 3 more Smart Citations
“…The presence of a band at 547 and 748 cm −1 in the spectra is a fingerprint of zinc-oxide vibration that underwent structural changes from the 471-614 cm −1 identified in the spectra of uncoated TM@ZnO NPs. Other authors also reported similar peaks indicating the surface coating of ZnO NPs with chitosan biopolymer [21,28,43,46]. The spectral profiles of TM@ZnO/TMC NC hydrogel on interaction with E. coli underwent some conformational changes in the broad peaks assigned to the stretching vibrations of the amines and -OH (3000-3129 cm −1 ).…”
Section: E Coli-tm@zno/tmc Nc Hydrogel Adsorption Interactionmentioning
confidence: 54%
“…Also, Aqueous Piper beetle leaf extract was reported by Thi Tran [41] to mediate the formation of a spherical shape ZnO NPs. A spherical/cubic and hexagonal shape for the ZnO NPs prepared from the extracts of Mentha pulegium were reported in a study to give a particle size distribution of 320 nm on the surface coating with chitosan [21]. Similarly, ZnO NC coated with chitosan (chitosan-ZnO) was observed to show a dendritic floc-like structure in a study reported by Bashal [28].…”
Section: Characterization Of Tm@zno/tmc Nc Hydrogelmentioning
confidence: 82%
See 2 more Smart Citations